Effect of experimental hyperbilirubinemia on visual system in rat brain - Siddiqui, Mohammad Shakil; Mansor, Othman; Singh, Mutum Samarendra (1999)
The average serum bilirubin concentration in the control and the hyperbilirubinemic group was 0.19 mg% and 3.39 mg% respectively.Gross examination· of the brains the control and the experimental animals did not show bilirubin staining. The coronal sections of brain passing through the caudal part of diencephalon showed the cavity of third ventricle lined by ependyma. Specialised elongated ependymal cells were seen in subcommissural organ (SCO). Posterior commissure (PC) was seen as bundle of transverse fibers dorsal to subcommissural organ. The lateral geniculate nucleus with dorsal (D) and ventral (V) parts was identified.